2022
DOI: 10.26434/chemrxiv-2021-ql3b7-v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bridging the Gap between H- and J-Aggregates: Classification and Supramolecular Tunability for Excitonic Band Structures in 2-Dimensional Molecular Aggregates

Abstract: Molecular aggregates with long-range excitonic couplings have drastically different photophysical properties compared to their monomer counterparts. From Kasha’s model for 1-dimensional systems, positive or negative excitonic couplings lead to blue or red shifted optical spectra with respect to the monomers, labelled H-and J-aggregates respectively. The overall excitonic couplings in higher dimensional systems are much more complicated and cannot be simply classified from their spectral shifts alone. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…The methanol solution of TDBC has a relatively low QY of 3%. [ 42,44 ] This is because of the flexible trimethine chain, where excited‐state C–C rotations act as a major nonradiative recombination pathway reducing the PL QY. [ 45,46 ] It has been shown that rigidification of the polymethine chain in many cyanine dyes using fused ring systems leads to a significantly improved PL QY.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methanol solution of TDBC has a relatively low QY of 3%. [ 42,44 ] This is because of the flexible trimethine chain, where excited‐state C–C rotations act as a major nonradiative recombination pathway reducing the PL QY. [ 45,46 ] It has been shown that rigidification of the polymethine chain in many cyanine dyes using fused ring systems leads to a significantly improved PL QY.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study the temporal dynamics of fluorescence, lifetime traces were obtained by integrating the emission across the wavelength range from 570–600 nm. The time‐resolved fluorescence decay of the monomer in methanol follows a biexponential curve with an 80 ps average lifetime, [ 42 ] whereas that of the freshly prepared J‐aggregates in water follows a monoexponential curve with a 130 ps lifetime (Figure 1G). Even though the monomer has a shorter lifetime than the J‐aggregate, most of the fluorescent decay in the monomer is because of nonradiative recombinations as evidenced by the low 3% QY.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations